(3x + 1)(x - 5)
(4x + 1)(2x + 3)
14x squared minus 7x to the 3rd power can be factored to 7x2(2-x).
7(x - 1)(x + 3)
7x2 - 14x = 7x(x - 2)
(2x + 5)(7x - 3)
14x(x + 2)
3x2 -14x -24 can be factored as (3x + 4)(x - 6).
Yes because if x2-14x+49 then it is (x-7)(x-7) when factored
14x2-7x2-16 7x2-16 (this can't be simplified any more)
if its x(squared) its 7x(cubed) if its 2xX its 14x(squared)
7x(3x3 - 2x2 + 5x + 1)
14x2 - 39x - 35 = (7x + 5)(2x - 7)
x2 + 14x + 45 = (x + 9) (x + 5)
As written, that equals 325 - 14x which is in its simplest form.
I suppose that would be 14x2 - 7x3. Just take out the common factor, 7x2. Divide each term by this factor to find the other factor.
(x - 16)(x + 2) x = 16 or -2
x2+14x+40 = (x+4)(x+10) when factored
x2 - 14x + 49(x - 7) (x - 7)
x2 - 14x + 45 = (x - 5)(x - 9).
(x - 4)(3x - 2)